Tradisi Ter-ater dalam Harmonisasi Sosial: Resolusi Konflik dalam Kontestasi Pilkades Bilapora Barat - Nur Fadiah Anisah (Retorik: Jurnal Ilmu Humaniora, 2022)
This study aims to see how the tradition of ter-ater (distributing something, usually food, to relatives and close neighbors) of the Madurese community is able to become a solution to the conflicts that arise during the Village Head Election (Pilkades) in West Bilapora. This study uses Max Weber's theory of action and the theory of hegemony offered by Gramsci. This research concludes that ter-ater can have direct implications in the conflict of two or more parties, if it is carried out by people in power who become community leaders. During the pre-election period, giving ateran to rivals is almost an error, which engenders misgivings. However, giving ateran to the people will generate sympathy for the candidate. Post-election, ter-ater can become a symbol for the village head's effort to open "new doors" toward social harmonization.